Blue printing in assessment of formative examinations of undergraduate medical students in pathology - Vahini, Gudeli; P. Umarani, P. Umarani; Sushma, Venkata (Journal of Neonatal Surgery, 2025)
Context/background: Assessment drives learning. Written examinations are the most employed method for assessment of cognitive skills in medical education lacking uniformity and validation. The few disadvantages of essay questions are a smaller number of questions, limited sampling, unfair distribution of questions over topics and vague questions. Blueprinting overcomes these issues, increasing the validity of examinations. Blueprinting has been a content validity tool. Aims and objectives: To describe the process of developing a blueprint for undergraduate formative examinations in pathology and to evaluate its effect as a tool to increase the content validity of assessment. Methodology: In present study, last five years ASRAMS second year MBBS pathology formative assessment papers in pathology were evaluated for its content validity. Desired weightage to all the topics in pathology were given by the faculty of the pathology. The formative assessment papers were also evaluated for level of cognitive domain. Closed ended feedback from faculty and second MBBS students was taken and statistically evaluated. Conclusions: Students were satisfied as blueprinting helped them to attempt examination better. The faculty who validated the blueprint felt that it helps in distribution of appropriate weightage and questions across the topics and blueprinting should be an integral part of assessment. Assessment should be aligned to learning objectives and blue printing improves content validity.